Investigation of the impact and post-impact behaviour of glass and glass/natural fibre hybrid composites made with various stacking sequences: Experimental and theoretical analysis. (March 2022) - Selver, Erdem; Dalfi, Hussein; Yousaf, Zeshan
In the present work, impact and post-impact response of thermoset composite laminates manufactured from glass, flax, jute fabrics and their hybrid combinations (glass/jute and glass/flax) made with various stacking sequences was studied. The low-velocity impact response of these laminates was investigated by drop-weight impact tests at different energy levels (20–50 J). Additionally, their post-impact behaviour was studied by compression after impact tests, measuring their residual compressive strength. Impact test results showed that glass composites had higher impact resistance than natural and hybrid composites. Moreover, the hybrid composites with glass fabric layers in the exterior resulted in better impact resistance compared to composites where glass fabric layers were placed in the interior with flax or jute fabrics. It was also observed that natural and hybrid composites absorbed more energy than that of glass composites between 20 and 40 J. Glass composites exhibited higher compression and compression after impact strength than natural and hybrid composites. However, hybrid composites had higher compression after impact strength retention (%) than glass composites due to less fibre damages. The numerical analysis was also conducted to simulate the intra-laminar damages and delamination failures. Good agreement was observed between numerical and experimental results.